THE IMPACT OF TURNAROUND TIME AND MRO FACILITY IN AIRCRAFT MAINTENANCE ON EMPLOYEE PERFORMANCE - Ade Ryan Setiawan; Timotius FCW Sutrisno; Natalia Christiani (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of Turnaround Time and MRO Facility on Employee Performance in aircraft maintenance activities. Optimal Turnaround Time and adequate maintenance facilities play a crucial role in enhancing Employee Performance, particularly in efficiency, job satisfaction, and productivity. The research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the Blindfolding technique to assess the model's predictive validity. Data were collected through questionnaires from employees involved in aircraft maintenance activities. The results indicate that TAT has a significant moderate effect on employee performance, suggesting that effective turnaround time management enhances work efficiency and overall employee productivity. Meanwhile, the MRO Facility also shows a statistically significant, albeit small, effect on employee performance, indicating that modern and well-equipped facilities contribute positively to performance outcomes. This study contributes theoretically to understanding the key factors affecting employee performance in the MRO sector and offers practical implications for management in optimizing performance improvement strategies. The study is limited by its narrow research scope and exclusion of other potential influencing variables. Future research is recommended to expand the study area and include additional variables such as job satisfaction, leadership style, and organizational culture.